ANALISIS STRATEGI PENGELOLAAN USAHA ARANG DI DESA PURWODADI KECAMATAN RIMBO BUJANG - Youdhi Prayogo; Eri Nofriza; Yuni Eva Purwanti (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research discusses the analysis of charcoal business management strategies in Purwodadi village, Rimbo Bujang subdistrict. The aims of this research are: First, to find out the strategy for managing the charcoal business in Purwodadi village, Rimbo Bujang sub-district. Second, to find out the obstacles and solutions in managing the charcoal business in Purwodadi village, Rimbo Bujang subdistrict. This research uses primary and secondary data, through observation, interviews and documentation. To achieve the objectives of this research, qualitative research was used, qualitative analysis using data reduction, data presentation and drawing conclusions. The results of research on charcoal business management were carried out in several stages. The stages used in the management process include Planning, Organizing, Actuating, Controlling. Business owners are also worried about obstacles and what solutions will be used in the process of managing a charcoal business.